Exploring nutritional compositions, volatile compounds, health benefits, emerging processing technologies, and potential food products of glutinous rice: a review - Mohd Ali, Maimunah; Hashim, Norhashila (Elsevier B.V., 2024)
Glutinous rice (Oryza sativa var. glutinosa) stands out as one of the most popular rice varieties globally, amidst thousands of rice cultivars. Its increasing popularity is attributed to its rich nutritional compositions and health benefits. This review aims to summarize the nutritional compositions, volatile compounds, and health benefits of glutinous rice. Further, in-depth studies are necessary to explore the utilization of glutinous rice in enhancing processing technologies and developing new food products. Glutinous rice has been shown to possess numerous health benefits, including antioxidant activity, bioactive compounds, anti-cancer properties, anti-inflammatory effects, anti-diabetic potential, and cholesterol-lowering effects. Besides its nutritional compositions, the major volatile compounds identified in glutinous rice could serve as a functional food for human consumption. Emerging processing technologies related to glutinous rice are elaborated to improve the latest developments for incorporating them into various food products.